COMPARISON OF LEUCOSITE DECREASE DUE TO THE USE OF FOLFOX AND FOLFIRI CHEMOTHERAPY REGION IN COLORECTAL CANCER PATIENTS AT A PRIVATE HOSPITAL IN BANDUNG, THE PERIOD OF 2021: PERBANDINGAN PENURUNAN LEUKOSIT AKIBAT PENGGUNAAN REGIMEN KEMOTERAPI FOLFOX DAN FOLFIRI PADA PASIEN KANKER KOLOREKTAL SALAH SATU RUMAH SAKIT SWASTA DI BANDUNG PERIODE TAHUN 2021 - Yovita Mercya; Lidya Marthan (Jurnal Kesehatan, 2022)
Colorectal cancer is the third most common type of cancer in the world. Chemotherapy is one of the treatments for colorectal cancer with the most widely used regimens known as FOLFOX and FOLFIRI. One of the most common side effects of chemotherapy from these two regimens is leukopenia. This study aims to examine the characteristics of age, gender, use of the regimen, the decrease in the leukocyte value of each regimen and the difference in the decrease in the leukocyte value from the use of the FOLFOX and FOLFIRI regimens. This research is an observational study, which was carried out retrospectively with total sampling and quantitative descriptive analysis. The data was taken from medical records of colorectal cancer patients who underwent chemotherapy with the FOLFOX and FOLFIRI regimens at one of Bandung Private Hospital for the 2021 period. The results of this study showed that colorectal cancer patients were most dominant at the age of 56-65 years as much as 50% and suffered by mostly male patients as much as 64.3% with the use of both regimens in the same amount, that is 50% each. After undergoing the first chemotherapy, there was a significant decrease in leukocyte values in both regimens. The mean percentage reduction in leukocytes with the use of FOLFOX was 19% and FOLFIRI was 28%, but statistically, the decrease in leukocyte values in the two regimens was not significantly different.